Penggunaan Ekstrak Buah Hutung (Barringtonia Asiatika) Untuk Mengendalikan Hama Maruca Testulalis Penggerek Polong Pada Kacang Panjang - Riski Siahaya; Victor George Siahaya; Marthin Kalay; Abraham Talahaturuson (Faculty of Agriculture, Pattimura University, 2017)
The use of synthetic chemicals to control plant pest should to be limited by utilizing natural products so that environmental contamination can be reduced and crop yields are safe to eat. The aim of this research is to get the effective concentration and application time of hutung fruit (Barringtonia asiatika) extract to control Maruca testulalis pod borer on long bean. The experiments design was complety randomized block design with treatments of 5% extract of hutung fruit with interval of time of two days application, 5% extract of nutmeg with time interval of three days application, 10% extract of nutmeg with time interval of two days application, 10% fruit extract hutung with a three-day application time interval. Two control treatments were 0.1% Decis insecticide with a three-day application time interval three replications and without any treatment. The result showed that 10% hutung fruit extract with two days application time interval was the best treatment and could decrease the intensity of Maruca testulalis pest borer attack on long bean up to 39,14%.